Current Topics in Echinococcosis - Rodriguez-Morales, Alfonso J. (IntechOpen, 2015)
Echinococcosis remains an important cause of morbidity and mortality in certain areas of the world, tropical and non-tropical, particularly in rural settings. This book includes different topics with regard to the epidemiology, biology, clinical manifestations, treatment and prevention of the wide spectrum of diseases caused by the different species of Echinococcus involved in human and animal infection, with an aim to update the most significant research in many of them as well as to offer a multinational perspective on different aspects. The book has been organized into three major sections: (I) Epidemiology; (II) Biological and Clinical Aspects; and (III) Treatment and Prevention. Section I includes topics covering epidemiological studies in Colombia, Chile, Mexico and Tunisia, including molecular biology approaches to the study of parasite species. Section II includes topics covering the biology of some Echinococcus species affecting mainly animals, as also the human clinical manifestations in the central nervous system (CNS), genitourinary tract and other organic typical and atypical locations, as well as radiological manifestations of pulmonary disease. Section III includes topics on the usefulness of immunotherapy for antihelmintic treatment and intervention strategies.